Surgical Treatment of Nonmineralized Supraspinatus Tendinopathy in Dogs: A Retrospective Long-Term Follow-Up - Adele Piras, Lisa; Olimpo, Matteo; Lafuente, Pilar; Tomba, Anna; Del Magno, Sara; Lardone, Elena; Peirone, Bruno; Mancusi, Davide (Animals, 2023)
(1) Background: two forms of supraspinatus tendinopathy (ST) have been reported in dogs: mineralized and non-mineralized. Surgical treatment consists of longitudinal incisions (splitting) in the tendon of insertion of the supraspinatus muscle. The purpose of this retrospective study is to describe the diagnostic workout, the surgical procedure and the short and long term follow up of dogs treated for non-mineralized ST. (2) Methods: medical records (2010–2017) of dogs diagnosed with non-mineralized ST that underwent surgical treatment were reviewed. Data retrieved were: signalment, history, clinical signs, orthopaedic examination findings, diagnostic imaging findings, surgical treatment, histopathologic diagnosis and clinical outcome. (3) Results: A total of 27 dogs met the inclusion criteria. The most consistent clinical findings were intermittent lameness accompanied by pain on palpation of the insertion of the supraspinatus. Magnetic resonance imaging (MRI) of 27 shoulders distended sheaths of the biceps tendon (10/27), compression of the biceps brachii tendon sheaths (5/27) and enlargement of the supraspinatus tendon (3/27) were observed. The most prominent histologic finding was severe myxomatous degeneration in all 27 samples. Resolution of lameness was achieved in 80% of the cases surgically treated without any further lameness episodes in the long-term follow-up. (4) Conclusions: the surgical splitting of the non-mineralized supraspinatus tendon is an effective procedure with no intra-operative complications and a low incidence of minor (18%) and major (4%) complications.
Keywords: arthroscopy; supraspinatus; tendinopathy; Scopus; JCR